2021
DOI: 10.1016/j.tranon.2020.100983
|View full text |Cite
|
Sign up to set email alerts
|

Addition of TLR9 agonist immunotherapy to radiation improves systemic antitumor activity

Abstract: Highlights High-dose RT upregulated pDCs within the tumor microenvironment. The administration of intratumoral TLR9 agonist (CMP-001) after stereotactic RT significantly enhanced the anti-tumor immune response both locally and at secondary tumor site. CMP-001 Post-RT delayed the abscopal tumor growth and extended the survival rate via increasing the percentages of activated CD4 + and CD8 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Thus, an alternative maximization strategy for ISV should be incorporation of local therapeutic interventions that accelerate tumor antigen release. ISV could be combined with radiotherapy 47 , photodynamic therapy 48 , thermal ablation 49 , irreversible electroporation 37 , 50 , cryoablation 51 or the recently developed near-infrared photoimmunotherapy. As our previous results showed that ICD is induced by K3-SPG itself 21 , these additional interventions would synergize with K3-SPG.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an alternative maximization strategy for ISV should be incorporation of local therapeutic interventions that accelerate tumor antigen release. ISV could be combined with radiotherapy 47 , photodynamic therapy 48 , thermal ablation 49 , irreversible electroporation 37 , 50 , cryoablation 51 or the recently developed near-infrared photoimmunotherapy. As our previous results showed that ICD is induced by K3-SPG itself 21 , these additional interventions would synergize with K3-SPG.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Radiotherapy can paradoxically promote tumor growth and invasion through the recruitment and repolarization of TAMs at the tumor site, limiting the efficacy of radiotherapy. 62 This can be highlighted by the use of liposomal clodronate to deplete macrophages before ionizing radiation. The effect on TAMs depends on the dosage used, whether low doses (below 1 Gy) or high doses (above 10 Gy).…”
Section: Trends In the Clinical Trials Of Combination Therapymentioning
confidence: 99%
“…The highly expressed postradiation TGFβ cytokine is supposed to have an immunosuppressive function that could be targeted by inhibitors to evoke more effective SRT-induced T cell antitumor activity, as evidenced by the CD8+ cells increase and immunosuppressive T regulatory cells decrease in peripheral blood of SRT-treated patients affected by HCC and administered with a well-tolerated TGFβ-specific blockade (galunisertib) [96]. A toll-like receptor 9 agonist was also successfully tested in metastatic lung adenocarcinoma in mice in order to turn off the immunosuppressive effects of high radiation doses (12 Gy × 3 fractions) so as to clearly prevail tumoricidal ones [97]. High radiation doses combined with immunotherapies are able to break through the wall of radioresistance of some tumors, such as renal cell carcinoma, notoriously refractory to conventionally fractionated radiotherapy, and also improve systemic control by producing abscopal effects [98].…”
Section: High Dose Per Fraction Radiotherapy and Immunotherapy: The Most Recent Evidence For A Successful Cooperationmentioning
confidence: 99%